Festschrift für Manfred Seebode zum 70. Geburtstag am 15. September 2008 - Schneider, Hendrik; Kahlo, Michael; Klesczewski, Diethelm; Schumann, Heribert (De Gruyter Recht, 2008)
Biographical note: Hendrik Schneider, Universität Leipzig; Michael Kahlo, Universität Leipzig; Diethelm Klesczewski, Universität Leipzig; Heribert Schumann, Universität Leipzig.
Includes bibliographical references
Keywords: Seebode, Manfred -- 1938-; Bibliografie; Aufsatzsammlung; Festschrift; Strafvollzugsrecht; Deutschland; Strafverfahrensrecht; Strafrecht; Seebode, Manfred